Maintenance Training as a Dynamic Capability Explaining Safety Performance in Kenya’s Aviation Industry - Paul Ombati; Tonny Lukose; Gloria Muthoni (PT Agung Media Publisher, 2026)
Safety performance remains a critical outcome in the aviation industry, where maintenance errors are frequently associated with incidents, delays, and operational disruptions. While prior studies emphasize technical training, limited attention has been given to maintenance training as an organizational capability that enhances safety outcomes, particularly in developing aviation environments. This study investigates how maintenance training dimensions influence safety performance in Kenya’s aviation industry. Guided by Dynamic Capabilities Theory and Human Factors Theory, the study adopted an explanatory research design using structured questionnaires administered to maintenance engineers working in 26 Approved Aircraft Maintenance Organizations and 9 domestic airlines operating at Wilson Airport, Kenya. A census approach produced 142 valid responses. Data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. The findings show that maintenance training significantly predicts safety performance, with the regression model explaining 73.6% of the variance (R² = 0.736). The model was statistically significant (F = 102.621; p < 0.001). All training dimensions positively influenced safety performance: training simulators (β = 0.316), training capacity (β = 0.278), leadership support (β = 0.263), and training frequency (β = 0.226). These results indicate that both technological resources and organizational support systems are essential in improving aviation safety outcomes. The study concludes that maintenance training operates as a dynamic organizational capability rather than a routine operational function. Continuous investment in simulators, instructor capacity, leadership commitment, and recurrent training strengthens competence renewal, reduces human error risk, and improves safety performance. The findings provide practical implications for regulators, airline managers, and maintenance organizations seeking to enhance safety through capability-driven training systems in developing aviation contexts.